The measurement of Lamb wave phase velocity using analytic cross-correlation method. (April 2021) - Zeng, Liang; Cao, Xuwei; Huang, Liping; Luo, Zhi
Highlights: An analytic cross-correlation method for Lamb wave phase velocity measurement. It requires measurements at only two adjacent positions. It demonstrates a great robustness to the measurement noises. Abstract: This paper is devoted to a method for the measurement of Lamb wave phase velocities when the material properties and the thickness of the structure are unknown. In that method, the key of phase-velocity dispersion determination is to achieve an accurate estimation of the group delay and the phase shift at each frequency point. Firstly, a typical chirp excitation is utilized, providing Lamb wave responses at a wide range of frequencies and with a high signal-to-noise ratio. Thus a series of narrowband responses at multiple frequencies could be obtained from a single testing. Subsequently, the analytical cross-correlation method is applied to determine the group delay and phase shift, which only requires measurements at two adjacent positions. On this basis, the phase velocity value at each frequency is calculated from the relations between the propagation distance, group delay and phase shift. The performance of the proposed method is analysed by simulated signals, and validated using experimental signals from an aluminum plate and a carbon fiber-reinforced polymer (CFRP) laminate. Those demonstrate the main advantage of the proposed method that it is quite efficient and simple on both testing and processing.